Finansal okuryazarlığın işletme performansına etkisinde finansal erişimin aracılık rolü - Tekin, Gökhan (Hasan Kalyoncu Üniversitesi, 2020)
Finansal okuryazarlık kavramı KOBİ'lerin kurulması, yönetimi ve başarısı için gerekli olan temel yetkinliklerden birisi olarak tanımlanmaktadır. Buna rağmen ülkemizde KOBİ'lerde finansal okuryazarlık ve işletme performansı arasındaki ilişki üzerine yapılan ampirik çalışmalar azdır. Bu çalışmada TRC1 Bölgesinde (Gaziantep-Adıyaman ve Kilis) faaliyette bulunan KOBİ'lerin performansı ile finansal okuryazarlık ve finansal erişim arasındaki ilişki ortaya konulmuştur. Araştırma kapsamında TRC1 bölgesinde yer alan KOBİ statüsünde faaliyette bulunan 395 firma sahibi/yöneticisi ile yüz yüze görüşülerek anket tekniği ile veri toplanmıştır. Çalışmada kullanılan ölçekler, 5'li Likert tipindedir. Analiz sonucunda elde edilen bulgulara göre finansal okuryazarlık işletme performansını pozitif yönde istatistiksel olarak anlamlı şekilde etkilemektedir. Finansal okuryazarlık finansal erişimi pozitif yönde anlamlı etkiler hipotezi de desteklenmiştir. Ayrıca finansal okuryazarlığın işletme performansı üzerinde dolaylı etkisinin anlamlı olduğu, dolayısıyla da finansal erişimin finansal okuryazarlık ile işletme performansı arasındaki ilişkiye aracılık ettiği tespit edilmiştir. Son olarak KOBİ'lerin finansal okuryazarlık ve finansal erişim düzeylerinin firmaların faaliyet süresine göre, işletmelerin personel sayısına göre, işletmelerin yasal statüsüne göre ve finans departmanının mevcudiyet durumuna göre anlamlı farklılık gösterdiği tespit edilmiştir.

Financial literacy has been identified as one of the major competencies required for the establishment, management and success of SMEs. However, there is almost no empirical studies on the relationship between financial literacy and SMEs' performance in Turkey, hence the need for further research in this area. This study sought to establish the relationship between entrepreneur financial literacy, financial access and performance of SMEs in Gaziantep, Adıyaman and Kilis. The study was guided by three objectives namely; to establish the relationship between entrepreneur financial literacy and performance of SMEs; to determine the relationship between entrepreneur financial literacy and financial access; to establish the influence of financial access on the relationship between financial literacy and performance of SMEs. The study population comprised of all SMEs in TRC1 Region, from which a representative sample of 395 SMEs was drawn. The main study instrument was a questionnaire which comprised of likert-type scale questions on the main variables of the study. The findings of the study indicated that entrepreneur financial literacy had a statistically significant influence on enterprise performance therefore the hypothesis that financial literacy influences enterprise performance was supported. The study also established that financial literacy had a statistically significant influence on financial access therefore the hypothesis that financial literacy influences financial access was supported. The study also revealed that intervening influence of financial access on the relationship between entrepreneur financial literacy and performance of SMEs was statistically significant. Further, the results revealed that level of financial literacy and financial access of SMEs change according to the duration of the firms, the number of employees of the enterprises, the legal status of the enterprises and the existence of a separate financial department of the enterprises.
The mediating role of financial access in the effect of financial literacy on firm performance
Keywords: İşletme; Business Administration